Spaghetti Meat Abnormality in Broilers: Current Understanding and Future Research Directions - Baldi, Giulia; Soglia, Francesca; Petracci, Massimiliano (Frontiers in Physiology, 2021)
Spaghetti meat is a recent muscular abnormality that affects the Pectoralis major muscle of fast-growing broilers. As the appellative suggests, this condition phenotypically manifests as a loss of integrity of the breast muscle, which appears soft, mushy, and sparsely thigh, resembling spaghetti pasta. The incidence of spaghetti meat can reach up to 20% and its occurrence exerts detrimental effects on meat composition, nutritional value, and technological properties, accounting for an overall decreased meat value and important economic losses related to the necessity to downgrade affected meats. However, due to its recentness, the causative mechanisms are still partially unknown and less investigated compared to other muscular abnormalities, for which cellular stress and hypoxia caused by muscle hypertrophy are believed to be the main triggering factors. Within this scenario, the present review aims at providing a clear and concise summary of the available knowledge concerning spaghetti meat abnormality and concurrently presenting the existing research gaps, as well as the potential future developments in the field.